Geopolitics of Connectivity: The EU in Central Asia - Sergey V. Mazanik; Tatiana A. Romanova (Vestnik RUDN. International Relations)
The articulation of the concepts of strategic sovereignty and strategic autonomy in the official discourse of the European Union (EU) is indicative of its geopolitical turn. In this context, the purpose of this article is to clarify how the EU politically redefines the Central Asian space as part of its connectivity strategy (EU Strategy for Connecting Europe and Asia). The theoretical framework of the study is based on critical geopolitics, which, through a discourse analysis approach, makes it possible to identify the changes that EU representatives make in the spatial representation of Central Asia and the dynamics of the significance of this region in the EU’s connectivity strategy. First, critical geopolitics will be operationalized with an emphasis on analytical categories such as discourse, hegemony, identity and ontological security. Thereafter, drawing upon the long-standing academic tradition of considering the EU as a geopolitical actor, the paper clarifies how, under the sway of the ongoing debate on strategic sovereignty (autonomy), the EU deploys the logic of inclusion and exclusion in its relations with third countries. Subsequently, the European connectivity concept will be outlined and the transformation of Central Asia’s role within the framework of the EU’s connectivity strategy will be revealed. The study found that, in the EU’s official discourse, connectivity, which is characterized by both normativity and securitization, is a tool for achieving resilience for the EU and its partners in Central Asia, a means of protecting them from third countries’ attempts to politically and economically weaponize interdependence, a way of preserving the so-called rules-based order as a resource of the EU’s global normative influence, and a way of achieving strategic autonomy that the EU is willing to export as a model. The inclusion of Central Asia in the concept of EU connectivity and the exclusion of other actors promoting their own models of governance and connectivity in this region can turn Central Asia into one of the most important areas of normative confrontation between the EU and the proponents of an alternative world order.